The ESTIMATING MARRIAGE AND DIVORCES AND COMPARING THEM USING NUMERICAL METHOD - Farah Feasal Ghazi; Rasha Ibrahim Khalaf; Sabah, Neeran (Al-Qadisiyah Journal of Pure Science, 2020)
In this paper, we describe the cases of marriage and divorce in the city of Baghdad on both sides of Rusafa and Karkh, we collected the data in this research from the Supreme Judicial Council and used the cubic spline interpolation method to estimator the function that passing through given points as well as the extrapolation method was applied to estimate the cases of marriage and divorce for the next year and comparison between Rusafa and Karkh by using the MATLAB program.